In-Situ Reforming of Tar from the Rapid Pyrolysis of a Brown Coal over Char - Matsuhara, T.; Hosokai, S.; Norinaga, K.; Matsuoka, K.; Li, Chun-Zhu; Hayashi, J. (American Chemical Society, 2010)
Reforming of nascent tar from the rapid pyrolysis of a brown coal over char prepared from the same coal was studied at 750−900 °C. The reforming was very rapid and extensive, allowing only benzene (0.02% on a coal C basis), naphthalene (0.001%), and phenanthrene (0.0001%) to escape from the char bed at an empty-bed gas residence time of less than 170 ms and 900 °C, respectively. Reforming even at 750 °C converted 96% of heavy tar (boiling point temperature >336 °C) into noncondensable gases and coke deposit over the char. Decreasing conversion of the tar into coke with increasing temperature suggested that the tar was reformed in a sequence of coking and steam gasification of the coke rather than direct steam reforming over the char. The reforming at 900 °C gave a negative coke yield due to progress of coke/char gasification faster than the coke deposition. Results of this work thus showed a possibility of complete tar reforming by intensification of contact between the char and volatiles even in the absence of a catalyst.